Poverty and Social impact Analysis : Strengthening Safety Nets in Djibouti - World Bank Group (Washington, DC, 2015)
This Poverty and Social Impact Analysis (PSIA) is part of a broader dialogue on energy tax reform and strengthening social safety nets in Djibouti. As part of a possible reform of energy taxes in Djibouti, the government of Djibouti has sought the support of the World Bank to better understand how such a policy reform can be pro-poor. The study was designed and implemented by a multisectoral committee composed of various stakeholder institutions, including the Ministry of Economy and Finance, the Ministry of Budget, the Secretary of State responsible for National Solidarity (SESN), the Department of Statistics and Demographic Studies (DISED), the Ministry of Energy, and the Ministry of Transport, with whom the teams of the Bank and the IMF collaborated throughout the process of preparation of the study. Technical meetings were held on January 30, February 2, May 25, May 28, and May 29, 2014, in Djibouti to discuss the various scenarios of reform, obtain additional information, and present preliminary quantitative results. Consultation meetings were held on July 2 and November 15, 2014, to present the findings and discuss possible reform options. This executive summary condenses the main findings of the study. The study is available as a separate report with more analyses and background information. The study is based on data from a representative household survey which includes detailed information on household expenditures and receipt of certain cash and in-kind benefits (EDAM 3-2012). The tables in this executive summary show 2014 prices, with inflation rates of 2.5 and 2.9 for 2013 and 2014, respectively.